Scientific Evidence of a Clash between Das Sollen and Das Sein in the book The Clash of Civilizations and the Remaking of World Order by Samuel P Huntington - Nur Rohim Yunus (JOURNAL of LEGAL RESEARCH, 2022)
Conflicts between nations that adhere to distinct worldviews will continue to shape the course of world politics in the foreseeable future. Culture, not politics or economics, will drive future wars on a global scale; these two factors are becoming increasingly irrelevant. This battle, in turn, will be the most significant symptom that replaces the polarization of world ideology into communist and capitalism, together with the collapse of the governmental system in the vast majority of Eastern European countries. The following are some of the factors that, according to Huntington, would cause conflicts between different civilizations in the future of world politics: 1). Differences in culture, tradition, and ethnicity, as well as differences in people's perspectives on how humans should relate to God, are all part of what distinguishes one civilization from another. These philosophical differences are at the root of the fact that people of different civilizations have different perspectives on how humans should relate to God. 2). In the sense that the interaction between various peoples and civilizations is continuing to rise, we might say that the world is continuing to become a smaller place. When people connect with one another on a deeper level, their knowledge of their own civilization grows, and they become more attuned to the distinctions that exist between their culture and those of other civilizations. 3). People all across the world have been uprooted from their deep-seated roots of local identity as a consequence of the process of economic modernization and social development. This has occurred as a result of globalization. 4). The Western world has played a dual role, which has contributed to the development of civilization consciousness. This may be understood as a stronger sense of love for a belief in the identity of civilization that has been going on for a long time.